Late-Season Nitrogen Fertilizer Application in Soybean - G. R. Balboa; D. R. Hodgins; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2015)
Field experiments were conducted at the North Central Kansas Experiment Field near Scandia, KS, in the summer of 2014 to evaluate effect of late-season nitrogen (N) fertilizer application on modern soybean genotypes under dryland and irrigated environments. The main objective was to determine if the N application late in the season has an agronomical benefit to soybean producers. A unique fertilizer N source (urea) was applied at five N rates (0, 40, 80, 120, and 160 lb N/a) to soybean at the R3 growth stage. Overall soybean yields under dryland conditions ranged from 73 to 89 bu/a, whereas yield variation in the irrigated environment was narrowed and ranged from 90 to 99 bu/a. Application of late-season N fertilizer did not significantly increase soybean yields either under full irrigation or in the dryland environment. Under irrigation, maximum soybean yield was documented at 99 bu/a with the 0-N fertilizer rate, whereas dryland soybean yield was maximized at 89 bu/a with 120 lb N/a.
Keywords: soybean; late-season nitrogen fertilizer; yield